Molecular characterization of mosquitoes (Diptera: Culicidae) from the Colombian rainforest (2021)
A few studies have carried out the taxonomic and molecular characterization of sylvatic mosquito species in Latin America, where some species have been incriminated as vectors for arboviruses and parasites transmission. The present study reports the molecular characterization of mosquito species in the Sierra Nevada de Santa Marta, a natural ecosystem in the Northern coast of Colombia. Manual capture methods were used to collect mosquitoes, and the specimens were identified via classical taxonomy. The COI marker was used for species confirmation, and phylogenetic analysis was performed using the neighbor-joining method, with the Kimura-2-Parameters model. Aedes serratus , Psorophora ferox , Johnbelkinia ulopus , Sabethes chloropterus , Sabethes cyaneus , Wyeomyia aporonoma , Wyeomyia pseudopecten , Wyeomyia ulocoma and Wyeomyia luteoventralis were identified. We assessed the genetic variability of mosquitoes in this area and phylogenetic reconstructions allowed the identification at the species level. Classical and molecular taxonomy demonstrated to be useful and complementary when morphological characteristics are not well preserved, or the taxonomic group is not represented in public molecular databases.